Morphological comparisons of two pairs of easily confused species in subtribe Goodyerinae (Cranichideae; Orchidaceae) - Liu, Xia Qiao; Cheng, Quan Zhi; Tan, Yun Hong; Hsu, Chuan Tian; Tian, Zhen Huai (Phytotaxa, 2015)
Two yellow-lipped species of Zeuxine viz. Z. flava and Z. sakagutii and another pair of species of Rhomboda, R. moulmeinensis and R. fanjingensis, are so similar that they are frequently misidentified. In this paper, based on field observations, study of type specimens and protologues, illustrations and comparisons of these two pairs of confused species are provided to enable identification.